Oxytocin mobilizes midbrain dopamine toward sociality - Charlet, Alexandre; Grinevich, Valéry (Neuron, 2017)
Oxytocin and dopamine possess significant overlap in the modulation of life-essential behaviors. Here, Xiao et al. (2017) show that the activity of dopamine neurons of the ventral tegmental area and the substantia nigra is finely tuned by axonal release of oxytocin.